Generation of hepatocyte from mouse mesenchymal stem cells in Vitro - zedan, zahraa kamel; M. Salih, Shahlaa; M. Hussain, Shalal (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
This study was designed to generate hepatocyte cells from mesenchymal stem cells (MSCs) isolated from mouse bone marrow via using culturing protocols for this goal. Cells of MSCs were isolated by collecting the thigh bone of 50 albino mice, both femur and tibia were collected and cells were flushed from bones and MSCs have been isolated based on the ability of MSCs to adhere on plastic surfaces. MSCs reactivity to CD45, CD90, CD34 and CD105 were tested by immunocytochemistry. Isolated MSCs exhibited positive reactivity towars CD105 and CD90 cell surface markers. MSCs were negative for the hematopoietic surface markers including CD34 and CD45. Differentiation into hepatocyte was induced by adding hepatogenic specific growth factors (Hepatocytes growth factors (HGF), Fibroblast growth factor4 (FGF4), oncostatin M and dexamethasone) to the differentiation medium. Cells were examined after differentiation protocol and characterized using immunocytochemistry analysis for Albumin and alpha fetoprotein. Positive results were observed indicating the potential ability of the isolated bone marrow MSCs to differentiate into Hepatocytes.